2018
DOI: 10.3389/fnins.2018.00752
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Outcomes Following Brain–Computer Interface Intervention for Upper Extremity Rehabilitation in Stroke: A Randomized Controlled Trial

Abstract: Stroke is a leading cause of persistent upper extremity (UE) motor disability in adults. Brain–computer interface (BCI) intervention has demonstrated potential as a motor rehabilitation strategy for stroke survivors. This sub-analysis of ongoing clinical trial (NCT02098265) examines rehabilitative efficacy of this BCI design and seeks to identify stroke participant characteristics associated with behavioral improvement. Stroke participants (n = 21) with UE impairment were assessed using Action Research Arm Tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 56 publications
(137 reference statements)
0
40
0
2
Order By: Relevance
“…A total of 1015 records were screened, of which the full texts of 80 were assessed for eligibility. Finally, 33 studies were included in the current systematic review [6, 7, 15-17, 26, 35, 37, 46, 47, 49-71], of which 18 studies were of single-group design [26,37,[56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71], and 15 studies were of controlled-trial design [6, 7, 15-17, 35, 46, 47, 49-55]. In the current review, only studies with a controlled-trial design were included in our metaanalysis, and those with single-group designs were only included in our qualitative description.…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
“…A total of 1015 records were screened, of which the full texts of 80 were assessed for eligibility. Finally, 33 studies were included in the current systematic review [6, 7, 15-17, 26, 35, 37, 46, 47, 49-71], of which 18 studies were of single-group design [26,37,[56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71], and 15 studies were of controlled-trial design [6, 7, 15-17, 35, 46, 47, 49-55]. In the current review, only studies with a controlled-trial design were included in our metaanalysis, and those with single-group designs were only included in our qualitative description.…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
“…The use of motor imagery in VR-BCI is a good example of how these two technologies can potentially be combined. Although a large part of the research combining these techniques has been in healthy participants (e.g., Ortner et al, 2012;Lupu et al, 2018;, or is still at proof-of-concept stage (Aamer et al, 2019), early clinical studies have shown promise for neurorehabilitation (Remsik et al, 2018;Cohen et al, 2019;Vourvopoulos et al, 2019). However, the spatiotemporal imprecision is currently a limiting factor.…”
Section: Future Developments In Therapeutic Vrmentioning
confidence: 99%
“…Participant characteristics are displayed in Table 1 . This interim analysis of the larger ongoing study seeks to elucidate the electrophysiological consequences and associations of BCI participation and the authors focus specifically on the behavioral (primary outcome) associations in another manuscript published in tandem with this effort ( Remsik et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%